Efficiently self-healing boronic ester crystals. Issue 10 (17th February 2020) - Commins, Patrick; Al-Handawi, Marieh B.; Karothu, Durga Prasad; Raj, Gijo; Naumov, Panče
Abstract : Organic crystal is described that can be bent plastically and twisted elastically, and can self-heal to 67%, an efficiency that is an order-of-magnitude higher compared to the only previously reported example. Abstract : The perception of organic crystals being rigid static entities is quickly eroding, and molecular crystals are now matching a number of properties previously thought to be unique to soft materials. Here, we present crystals of a boronate ester that encompass many of the elastic and plastic mechanical properties of polymers such as bending, twisting, coiling and highly efficient self-healing of up to 67%, while they maintain their long-range structural order. The approach utilizes the concept of dynamic covalent chemistry and proves it can be applied towards ordered materials. This work expands our current understanding of the properties of crystalline molecular materials, and it could have implications towards the development of mechanically robust organic crystals that are capable of self-repair for durable all-organic electronics and soft robotics.